2008
DOI: 10.1111/j.1574-6968.2008.01218.x
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus saprophyticusATCC 15305 is internalized into human urinary bladder carcinoma cell line 5637

Abstract: Invasion of bacteria into nonphagocytic host cells is an important pathogenicity factor for escaping the host defence system. Gram-positive organisms, for example Staphylococcus aureus and Listeria monocytogenes, are invasive in nonphagocytic cells, and this mechanism is discussed as an important part of the infection process. Uropathogenic Escherichia coli and Staphylococcus saprophyticus can cause acute and recurrent urinary tract infections as well as bloodstream infections. Staphylococcus saprophyticus sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 33 publications
2
32
0
1
Order By: Relevance
“…First, the maximal activation of NF-kB occurred prior to the maximal invasion of S. aureus in human osteoblasts. Since the quantitative analysis of bacterial invasion into non-professional phagocytes is an important pre-requisite to unravel the molecular details of pathogen-to-host cell interaction [15], in the present study, we used flow cytometry analysis with CFSE-labeled S. aureus as previously described [15,17] to quantify the kinetic invasion of S. aureus into human osteoblasts and to investigate the inhibitory effect of cytochalasin D or MDC on the invasion of S. aureus into human osteoblast. Our results indicated that the invasion of S. aureus into human osteoblasts increased for approximately 120 min following infection and that cytochalasin D (5 mg/ml) and MDC (0.6 mM) could inhibited the invasion of S. aureus into human osteoblasts by 99.81% and 96.63%, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the maximal activation of NF-kB occurred prior to the maximal invasion of S. aureus in human osteoblasts. Since the quantitative analysis of bacterial invasion into non-professional phagocytes is an important pre-requisite to unravel the molecular details of pathogen-to-host cell interaction [15], in the present study, we used flow cytometry analysis with CFSE-labeled S. aureus as previously described [15,17] to quantify the kinetic invasion of S. aureus into human osteoblasts and to investigate the inhibitory effect of cytochalasin D or MDC on the invasion of S. aureus into human osteoblast. Our results indicated that the invasion of S. aureus into human osteoblasts increased for approximately 120 min following infection and that cytochalasin D (5 mg/ml) and MDC (0.6 mM) could inhibited the invasion of S. aureus into human osteoblasts by 99.81% and 96.63%, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The invasion of S. aureus into human osteoblasts was quantified using flow cytometry analysis as described previously [15,17]. Briefly, osteoblasts were plated at 5 Â 10 4 cells/well in 12-well tissue culture plates and exposed to CFSE-labeled S. aureus at a multiplicity of infection (MOI) of 250 for different designated times.…”
Section: Bacteria Invasion Assaymentioning
confidence: 99%
“…Its virulence factors include the enzyme urease (Gatermann et al 1989), an adhesive and autolytic protein called Aas (Hell et al 1998), a collagenbinding protein designated SdrI (Sakinc et al 2006), and a surface-associated lipase called Ssp (Sakinc et al 2007). These latter proteins appear to allow the bacteria to attach to uroepithelial cells and to become internalized within them (Szabados et al 2008). While antibiotics such as b-lactams, sulfmethoxazole/trimethoprim, and fluoroquinolones can be used to treat urinary tract infections, resistant organisms are frequently recovered from infected individuals (Gupta 2003;Guay 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Shielded from the host immune system and from antibiotics in the bladder lumen, such bacterial reservoirs can persist and later emerge to initiate a fresh round of acute infection [4]. Recent studies have shown that UTI is also associated with other species of chronic, invasive bacteria besides E. coli, including Enterococcus faecalis [5][6][7].…”
Section: Introductionmentioning
confidence: 99%